Ants of the Genus SOLENOPSIS Westwood, 1840 (Hymenoptera: Formicidae) in Egypt with a description of the worker castes of S. cooperi Donisthorpe, 1947 - Sharaf, Mostafa R.; Taylor, Brian; Klingenberg, Christiana (Zootaxa, 2009)
The Egyptian species of the ant genus Solenopsis Westwood, 1840, are revised and keyed. Four species are recognized: S. cooperi Donisthorpe, 1947; S. lou Forel, 1902; S. occipitalis Santschi, 1911; and S. kochi Finzi, 1936 (stat. n.). Solenopsis occipitalis is recorded for the first time from Egypt. Solenopsis kochi is redescribed and elevated to species rank. Solenopsis bakri Sharaf, 2007 is synonymized under S. cooperi. The workers of S. cooperi are described for the first time, males and alate gynes are measured, and ecological notes on habitats are given. Available literature records of all the species are reviewed.